Faktor Yang Berhubungan Dengan Perilaku Berpacaran Remaja - Suci Fitriana Pramudya Wardani; Lili Retno Atika (STIKES Borneo Cendekia Medika, 2025)
The 2021 Adolescent Reproductive Health Survey shows that the group of adolescents aged 15-17 years have dated, where the percentage is 45.3% of male adolescents and 47.0% of female adolescents. Bad dating behavior in this case leading to premarital sex in adolescents is no longer a complex problem but has become a habit or tradition that can result in unwanted pregnancies and sexually transmitted diseases. This study aims to identify the factors influencing dating behavior among adolescents. Conducted as a cross-sectional study, the population included 340 students from SMKN 02 Songgom in 2023, with a sample of 184 respondents. Data analysis was performed using the chi-square test. The results indicated no significant relationship between age, place of residence, and dating behavior. However, a significant relationship was found between gender and dating behavior among adolescents. The role of parents or family is needed in providing information regarding good dating behavior, in order to avoid dating behavior that leads to premarital sex.